Frontispiece: Recent Advances in the Synthesis of Peptoid Macrocycles. Issue 30 (28th May 2018) - Webster, Alexandra M.; Cobb, Steven L.
Abstract : Macrocyclic peptoids : Developing medical applications for peptides has, and continues to be a highly active area of research, however, there are significant challenges associated with the development of peptide‐based therapeutics. Peptoids offer an alternative to peptides but the absence of any backbone hydrogen bonding means they exhibit a high degree of conformational flexibility. Cyclisation has been explored as one possible route to rigidify peptoid structures. This review outlines the recent strategies that have been developed to access new types of macrocyclic peptoids. For more details, see the Minireview by A. M. Webster and S. L. Cobb onpage 7560 ff.